Clinical Application of Ultrasound in the Diagnosis and Treatment of Reninoma - Qiuyang Li, MD, Ying Zhang, MD, Yong Song, MD, Aitao Guo, MD, Nan Li, BS, Yukun Luo, MD, Jie Tang, MD (Advanced Ultrasound in Diagnosis and Therapy, 2020)
Objectives: To investigate the clinical value of ultrasound in the diagnosis and treatment of reninoma.Methods: We retrospectively analyzed the ultrasound findings of 9 patients with reninoma confirmed by pathology after surgical resection in our hospital between September 2012 and August 2019. All patients underwent conventional preoperative ultrasonography. Three underwent contrast-enhanced ultrasound (CEUS) and 3 with complete endogenetic tumor underwent intraoperative ultrasonography.Results: Of the 9 patients with conventional ultrasound, 7 had renal space-occupying lesions and 2 had missed diagnosis. A hypoechoic or hyperechoic solid mass with regular morphology, clear boundary, capsule, weak echo halo around the mass, incomplete thin strip color blood flow signal around the mass were shown in 7 cases. Color Doppler displayed color flow signal of the incomplete thin strip around the mass and arterial blood supply with an internal thin branch. In 3 patients (including 2 with missing diagnosis by conventional ultrasound) who underwent preoperative contrast-enhanced ultrasound, the reninoma manifested as low enhancement, and the perfusion pattern showed as slow wash-in and slow wash-out compared with normal renal cortex. In 3 patients (including 2 cases of missed diagnosis by conventional ultrasound) with completely endogenic reninoma, intraoperative ultrasound clearly showed the tumor characteristics, and all successfully underwent laparoscopic ultrasound-guided partial nephrectomy.Conclusions: Preoperative conventional ultrasound combined with CEUS, and clinical features, are helpful for the qualitative diagnosis of reninoma. Laparoscopic partial resection is the first-choice treatment for reninoma. Intraoperative ultrasound can provide real-time imaging, accurately evaluate the tumor status, and provide important information for surgeons.